Design of a water quality information system for source water assessment: a Denver water case study, Denver, Colorado - Twenter, Justin C., author; Loftis, Jim C., advisor; Ward, Robert C., committee member; Smith, Freeman, committee member (Colorado State University. Libraries, 2002)
The questions water quality information systems are being called upon to answer are changing as the management of water quality shifts from a historically point source control framework to investigation of non point sources of pollution. A specific example is that of large Public Water Systems (PWS), providers of drinking water to the public within larger municipalities, who have managed the quality of the source water, from which they draw their supplies, primarily at the intake to the treatment system. In the case of contamination, the potential of finding a new source of supply is rare for large PWSs and thus new emphasis is placed on protection of current supplies to diminish the risk of contamination. This idea of moving farther up into the watershed for water quality management of drinking water supplies is presented by the U.S. Environmental Protection Agency (USEPA) in the Source Water Assessment and Protection (SWAP) program. This thesis proposes a process by which a large PWS can incorporate existing knowledge concerning water quality monitoring into a practical application for production of usable, defensible information used in the management of water quality. The source water quality monitoring system for Denver Water, a large PWS serving the City and County of Denver, Colorado and surrounding areas, is reviewed within this work. The review is presented as an updated water quality monitoring design for Denver Water’s entire source area. The emphasis of the design is placed on the need to connect the information needs of management, in this case Denver Water, with the feasible products of water quality monitoring. Analysis was conducted to determine reasonable sampling frequencies for estimation of mean concentrations, trends, and pollutant loads for physical and chemical water quality parameters identified. Additionally, 48 sampling sites were selected for the source area of approximately 2.5 million acres. In the end, Denver Water is presented a functional monitoring system which enables information production to meet needs for management of the vast area from where they draw drinking water.
Keywords: Denver (Colo.). Water Department; Water quality -- Colorado -- Denver Metropolitan Area; Drinking water -- Colorado -- Denver Metropolitan Area